PERSEPSI GURU TENTANG FAIRNESS DALAM ASESMEN PENDIDIKAN: STUDI KUALITATIF PADA GURU SEKOLAH MENENGAH DI INDONESIA - Shierly Luthfia Shalsa; Aprilia Rambe; Intan Baiduri; Rachmadiar Perdana; Hazatriningrum Kusumawati; Indri Hapsari (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
Fairness in educational assessment is a fundamental principle shaping the quality of teacher-student relationships and the meaningfulness of the learning process. A preliminary study conducted in several secondary schools in Jakarta, Semarang, and Banjarbaru found that some teachers still base their assessment practices on personal experience and institutional pressure, without a clear conceptual grounding in fairness. This study aims to explore in depth how secondary school teachers interpret and practice fairness in educational assessment. The study employed a qualitative approach using semi-structured interviews with five teachers from junior high, senior high, and vocational school levels in public schools. Data were analyzed using Braun and Clarke's six-phase thematic analysis, encompassing familiarization with the data, generating initial codes, searching for themes, reviewing themes, defining and naming themes, and producing the report. The findings reveal six major themes: teacher identity, emotion, and professional development; teacher-student relationships and classroom management; assessment systems and learning evaluation; curriculum and education policy; inclusive education and student diversity; and professional collaboration and learning innovation. The findings indicate that teachers' perceptions of fairness are neither singular nor static, but are dynamically constructed through the interaction of emotional experience, interpersonal relationships with students, curriculum policy demands, and the need to accommodate students with special needs. Teachers conceive of fairness not as uniform treatment, but as the adjustment of assessment to each student's condition, effort, and character. This study contributes to the development of a contextual fairness model for assessment that reflects the realities of education in Indonesia and provides a basis for designing teacher professional development programs related to fair assessment literacy. ABSTRAK Keadilan (fairness) dalam asesmen pendidikan merupakan prinsip penting yang menentukan kualitas hubungan antara guru dan peserta didik serta kebermaknaan proses belajar. Studi pendahuluan di beberapa sekolah menengah di Jakarta, Semarang, dan Banjarbaru menemukan bahwa sebagian guru masih mendasarkan praktik penilaian pada pengalaman pribadi dan tekanan institusional, tanpa pijakan konsep fairness yang jelas. Penelitian ini bertujuan untuk mengeksplorasi secara mendalam bagaimana guru sekolah menengah memaknai dan mempraktikkan fairness dalam asesmen pendidikan. Penelitian menggunakan pendekatan kualitatif dengan metode wawancara semi-terstruktur terhadap lima guru dari jenjang SMP, SMA, dan SMK di sekolah negeri. Data dianalisis menggunakan analisis tematik enam tahap dari Braun dan Clarke, meliputi pengenalan data, pembuatan kode awal, pencarian tema, peninjauan tema, penamaan tema, dan penyusunan laporan. Hasil penelitian mengungkap enam tema utama, yaitu identitas, emosi, dan pengembangan guru; hubungan guru-siswa dan manajemen kelas; sistem penilaian dan evaluasi pembelajaran; kurikulum dan kebijakan pendidikan; pendidikan inklusif dan keberagaman siswa; serta kolaborasi profesional dan inovasi pembelajaran. Temuan menunjukkan bahwa persepsi guru tentang fairness tidak bersifat tunggal dan statis, melainkan terbentuk secara dinamis melalui interaksi antara pengalaman emosional, relasi interpersonal dengan siswa, tuntutan kebijakan kurikulum, dan kebutuhan akomodasi bagi siswa berkebutuhan khusus. Guru memaknai keadilan bukan sebagai penyamaan perlakuan, tetapi sebagai penyesuaian penilaian terhadap kondisi, usaha, dan karakter masing-masing siswa. Penelitian ini memberikan kontribusi pada pengembangan model fairness dalam asesmen yang kontekstual dengan realitas pendidikan di Indonesia, serta menjadi dasar bagi penyusunan program pengembangan profesional guru terkait literasi asesmen yang adil.